The movement and forces of spinning solution in the nozzle during high-speed centrifugal spinning. (February 2019) - Duan, Yaoshuai; Zhang, Zhiming; Lu, Binbin; Chen, Boya; Lai, Zilong
High-speed centrifugal spinning is a novel method to fabricate nanofiber. It has the potential to fabricate nanofiber on a large scale because its production efficiency is much greater than traditional methods. Nozzle is an important part of high-speed centrifugal spinning equipment because its length, shape, and diameter all will affect the morphology and quality of nanofiber. It is useful to study the movement and forces of spinning solution in the nozzle. In this article, the principle and equipment structure of high-speed centrifugal spinning are briefly introduced at first. Then the movement and forces of spinning solution are analyzed by establishing parametric model at nozzle. It can be found that the spinning solution is ejected from nozzle when the rotating speed reaches a critical value. The critical rotating speed is inversely proportional to the radius of nozzle and directly proportional to the viscosity of spinning solution. There are several nozzle structures proposed and compared for nozzle optimization. Finally, the effects of nozzle parameters, concentration of spinning solution, and rotational speed on the morphology of nanofiber are verified by high-speed centrifugal spinning experiments. It lays the foundation for optimizing spinning equipment.